Detection, characterisation and risk factor of Leptospira spp. among dogs and dog handlers - Goh, Soon Heng (2022)
Leptospirosis is a re-emerging zoonosis commonly associated with dogs. However, serological diagnosis remains a challenge, especially among vaccinated dogs. Dogs pose a zoonotic threat potential to at-risk dog handlers, yet, there is limited knowledge regarding the potential risk factors and awareness levels among them. Therefore, this study determined; i) the post-vaccination antileptospiral antibody titres in healthy pet dogs and puppies, ii) the susceptibility of urban stray dogs in shedding Leptospira spp., iii) the seroprevalence and risk factors of leptospiral infection among dogs and dog handlers, and iv) the knowledge, attitude, and practice (KAP) towards leptospirosis among dog handlers. The median antibody titre in puppies was 1:100 (range: 1:50-1:200) with a median duration of 4 weeks (range: 2 weeks-9 months). For adult dogs the median antibody titre was 1:200 (range: 1:50-1:800)] with a median duration of 6 months (range: 6 weeks-1 year). Icterohaemorrhagiae titres was the highest with the longest duration followed by Canicola, Grippotyphosa and Pomona, with no cross-reaction detected throughout the sampling period for both groups. Among the urban stray dogs, 32.0% (n=32/100) was seropositive predominantly for serovars Javanica, Bataviae, Icterohaemorrhagiae, Autumnalis, Canicola, Pyrogenes, Copenhageni, and Australis (titres ranged: 1:100-1:800). Six Leptospira spp. isolates were procured from urine, kidney and liver samples of four dogs. Isolation and identification revealed the isolates were pathogenic L. interrogans serovar Bataviae (n=5) and Canicola (n=1). Among the working and shelter dogs, 26.3% (n=70/266) were seropositive predominantly for serovars Icterohaemorrhagiae, Ballum, Bataviae and Javanica (titres ranged: 1:100– 1:800). The potential dog risk factors identified were presence of rats [OR = 4.61 (95% CI: 1.05, 20.33), p = 0.043] and shared common area within the organisation [OR = 5.12 (95% CI: 1.94, 13.46), p = 0.001]. As for the dog handlers, 34.5% (n=67/194) were seropositive predominantly for serovars Grippotyphosa, Icterohaemorrhagiae and Malaysia (titres ranged: 1:50–1:200). Besides the known zoonotic risk from exposure to rats and a contaminated environment from, increased contact time with the dogs [OR = 3.28 (95% CI: 1.28, 8.40), p = 0.013] was identified as another important risk factor after controlling the other factors, which highlighted the potential transmission from dog to human. Awareness is important but unfortunately, most working dog handlers (58%, n=58/100) and shelter dog handlers (90%, n=34/38) lacked knowledge. Attitude towards leptospirosis was also poor among most working dog handlers (75%, n=75/100) and all shelter dog handlers. the working dog handlers (77%, n=77/100) had good practices while shelter dog handlers (47%, n=18/38), had moderate level. The poor knowledge was likely due to the lower education level. Lack of knowledge in terms of clinical sign of the disease will be a challenge for disease management. Despite the limited knowledge, they still know the importance of preventive measures such as vaccination in disease prevention. In conclusion, MAT remains a gold standard test for serological diagnosis and surveillance, however, detailed considerations should be taken when interpreting results of clinical cases with the presence of anti-leptospiral antibodies, as paired serum for better interpretation was required. Although the absence of circulating environmental serovars among urban stray dogs, nonetheless the zoonotic potential remains as they can still be infected or carriers of other pathogenic serovars and disseminate the disease via urine shedding. The diverse occupational responsibilities may predispose both dogs and their handlers towards exposure to both Leptospira spp. contaminated environments and infected/reservoir animals. Frequent close contact with their potentially infected dogs adds additional occupational risk for dog handlers. Such risk could be mitigated with proper protection when dog handling during operations. Promoting awareness through knowledge enhancements could limit the risk of disease transmission among animals and humans.